Connexin43 promotes angiogenesis through activating the HIF-1α/VEGF signaling pathway under chronic cerebral hypoperfusion. Issue 10 (October 2021) - Yu, Weiwei; Jin, Haiqiang; Sun, Wei; Nan, Ding; Deng, Jianwen; Jia, Jingjing; Yu, Zemou; Huang, Yining
Chronic cerebral hypoperfusion, a major vascular contributor to vascular cognitive impairment and dementia, can exacerbate small vessel pathology. Connexin43, the most abundant gap junction protein in brain tissue, has been found to be critically involved in the pathological changes of vascular cognitive impairment and dementia caused by chronic cerebral hypoperfusion. However, the precise mechanisms underpinning its role are unclear. We established a mouse model via bilateral common carotid arteries stenosis on connexin43 heterozygous male mice and demonstrated that connexin43 improves brain blood flow recovery by mediating reparative angiogenesis under chronic cerebral hypoperfusion, which subsequently reduces the characteristic pathologies of vascular cognitive impairment and dementia including white matter lesions and irreversible neuronal injury. We additionally found that connexin43 mediates hypoxia inducible factor-1α expression and then activates the PKA signaling pathway to regulate vascular endothelial growth factor-induced angiogenesis. All the above findings were replicated in bEnd.3 cells treated with 375 µM CoCl2 in vitro . These results suggest that connexin 43 could be instrumental in developing potential therapies for vascular cognitive impairment and dementia caused by chronic cerebral hypoperfusion.